2018
DOI: 10.12659/msm.908962
|View full text |Cite
|
Sign up to set email alerts
|

Polish Helicopter Emergency Medical Service (HEMS) Response to Out-of-Hospital Cardiac Arrest (OHCA): A Retrospective Study

Abstract: BackgroundOut-of-hospital cardiac arrest (OHCA) is a significant clinical challenge for emergency medical systems worldwide. The first step towards ensuring patient survival is achieving return of spontaneous circulation (ROSC). The purpose of the study was to analyze the cases of OHCA to which HEMS teams were dispatched.Material/MethodsWe performed a retrospective analysis of all HEMS calls in Poland for cases of OHCA between 1 January 2011 and 31 December 2016. Data were obtained from medical records maintai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 23 publications
0
13
1
Order By: Relevance
“…In a cohort study analyzing OHCA in 27 European countries, the prevalence of OHCA in a shockable rhythm was 22%, compared to 15% in our study. However, of the ROSC patients we analyzed, as many as 34% had VT/VF rhythms as the cause of OHCA; in other studies, 13 to 54% of the patients with ROSC showed shockable rhythms [9,16,23,24]. In our study, there were no statistically significant differences in ROSC according to gender, age, or the type of EMT.…”
Section: Discussioncontrasting
confidence: 67%
“…In a cohort study analyzing OHCA in 27 European countries, the prevalence of OHCA in a shockable rhythm was 22%, compared to 15% in our study. However, of the ROSC patients we analyzed, as many as 34% had VT/VF rhythms as the cause of OHCA; in other studies, 13 to 54% of the patients with ROSC showed shockable rhythms [9,16,23,24]. In our study, there were no statistically significant differences in ROSC according to gender, age, or the type of EMT.…”
Section: Discussioncontrasting
confidence: 67%
“…Similar results were obtained by Rzońca et al who analysed the missions of HEMS crews to out-of-hospital cardiac arrest in Poland. The study found that patients with return of spontaneous circulation were more often transported to hospitals by HEMS teams, and that the cases of death before the arrival of the HEMS team were more frequent [27]. Analysis of the authors' own research shows that the clinical status of the patients treated in rural areas was more severe than that of patients in urban areas, as indicated by the GCS scores (12.03 vs. 12.35), the RTS scores (10.14 vs. 10.60) and the NACA scores.…”
Section: Discussionmentioning
confidence: 92%
“…This survival chain consists of community, hospital-based services, and rapid deployment of an emergency physician and ambulances [3]. Although cardiopulmonary resuscitation is the first-and the main-line treatment for the cardiopulmonary arrest [4], the survival rate of the out-of-hospital cardiopulmonary arrest varies between 5 and 38%, and this difference is related to the way that the pre-hospital emergency medical services are managed [5]. Improving the quality as well as the effectiveness of care for the patients with the out-of-hospital cardiopulmonary arrest is addressed as one of the tasks of the emergency medical services throughout the world; however, these systems differ significantly in terms of structure and organization [5].…”
Section: Introductionmentioning
confidence: 99%